Perspektif Qira'Ah Mubadalah Terhadap Sikap Posesif Istri Kepada Suami - Nurkhovivah, Mahmudha; Khaidarulloh (Fakultas Syariah IAIN Ponorogo, 2024)
Domestic violence is a global problem, including in Indonesia, with a high This research started from a case of domestic violence which experienced disharmony in carrying out its rights and obligations resulting in a wife's possessive attitude towards her husband. The formulation of the problem in the research is 1. What is Qira>'ah Muba>dalah's perspective on forms of possessive attitudes of wives in interpersonal relationships between husband and wife in Kauman District, Ponorogo Regency? and 2. What is Qira'ah Muba>dalah's perspective on the rights and obligations of husband and wife in cases of possessive wives in Kauman District, Ponorogo Regency? This research is a type of qualitative field research. The analysis used in this research is descriptive analysis. The findings of this research show that the pattern of husband and wife relations in Kauman District, Ponorogo Regency, there is an imbalance in carrying out rights and obligations. The wife's possessive attitude creates discomfort and conflict, doubts the integrity of the family, and is contrary to the principle of Qira>'ah Muba>dalah. Marriage should be based on cooperation, mutual understanding, and balance in affection. A wife's possessive attitude which limits her husband in carrying out his obligations to earn a living can of course narrow the husband's career space and reduce his knowledge. This excessive control is not in line with Mubjadi's values ​​which emphasize mutuality, partnership and cooperation. Gender equality is important to maintain family harmony.